2011
DOI: 10.1016/j.envpol.2010.09.027
|View full text |Cite
|
Sign up to set email alerts
|

The physiological, transcriptional and genetic responses of an ozone- sensitive and an ozone tolerant poplar and selected extremes of their F 2 progeny

Abstract: Ozone-responsive transcriptional changes and genetic control were studied in Populus plants with contrasting ozone sensitivity. a r t i c l e i n f o a b s t r a c tRelatively little is known about the transcriptional response or genetic control of response and adaptation of trees to tropospheric ozone exposure. Such understanding is needed as up to 50% of forests, globally, may be subjected to phytotoxic concentrations of ozone. The physiological, transcriptional and genetic response to ozone was examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 69 publications
(70 reference statements)
2
36
0
Order By: Relevance
“…Chronic exposure to elevated O 3 causes biochemical changes, reduced growth, and morphological changes in several plant species (Skärby et al, 2004;Li et al, 2006;Karnosky et al, 2007;Kontunen-Soppela et al, 2010;Street et al, 2011). Similarly, chronic exposure to several other stresses causes similar growth changes.…”
Section: Ros-induced Morphological Responsesmentioning
confidence: 83%
“…Chronic exposure to elevated O 3 causes biochemical changes, reduced growth, and morphological changes in several plant species (Skärby et al, 2004;Li et al, 2006;Karnosky et al, 2007;Kontunen-Soppela et al, 2010;Street et al, 2011). Similarly, chronic exposure to several other stresses causes similar growth changes.…”
Section: Ros-induced Morphological Responsesmentioning
confidence: 83%
“…O 3 is an air pollutant that enters leaves through the stomata, where it rapidly forms other reactive oxygen species that cause damage to biochemical constituents and physiological processes, ultimately leading to reductions in leaf longevity and yield (Fiscus et al, 2005;Ainsworth et al, 2012). Past efforts to detect the genetic variation in O 3 tolerance using mapping populations have scored visible leaf damage or plant biomass (Kim et al, 2004;Frei et al, 2008;Brosché et al, 2010;Street et al, 2011;Ueda et al, 2015) but have not quantified the many other physiological changes that ultimately determine the impact of O 3 on crop yield. These include reduced photosynthetic capacity, reduced leaf chlorophyll and N content, accelerated senescence, increased antioxidant capacity, altered carbohydrate and metabolite content, decreased specific leaf area (SLA), and increased rates of respiration (Fiscus et al, 2005;Leitao et al, 2007;Dizengremel et al, 2008;Betzelberger et al, 2012;Gillespie et al, 2012).…”
mentioning
confidence: 99%
“…Large differences were found between poplar and Arabidopsis, which is flood-sensitive, in terms of metabolite and transcript patterns in response to hypoxia, accounting for the ability of poplar to maintain its carbon and energy metabolism and, thus, its flood tolerance (Kreuzwieser et al 2009). A QTL analysis associated with a study of transcriptional responses to ozone showed the involvement of key genes relating to ethylene production and response (Street et al 2011). As for model plants, most molecular studies of the response of trees to abiotic stresses have been conducted on leaf material (ESM_3.xls).…”
Section: Abiotic Stressesmentioning
confidence: 99%